Análise da carga viral e do estado físico do DNA-HPV 16 em amostras penianas - Maria Gabrielle de Lima Rocha (2013)
Although HPV infection in men is associated with low morbidity and mortality, the importance of its investigation should be highlighted due to association with anogenital cancer and genital warts, and the role that man plays in the transmission of HPV to their sexual partners. In this study we evaluated the viral load and integration of HPV-16 into the human genome in a hundred penile samples of men with condyloma acuminate or asymptomatic, but partners of women with high-grade lesion. These parameters were also studied in 9 penile carcinoma samples. HPV-16 genome was detected in 38% of penile samples analyzed. In majority of the infected men for this virus (90%), the HPV-16 genome presented with some degree of integration, as well as all the samples studied penile carcinoma, suggesting that integration can be an important factor for penile carcinogenesis. The integration of the HPV-16 genome does not appear, however, to be influenced by the presence of condyloma acuminate or multiple infections. Wide variation in viral load of HPV-16 was found (0.0003 a 5386.15 copies/ cell), independent of the physical state of the genome of this virus, whether integrated or episomal. The integration of the HPV-16 genome occurred in the presence of low or high viral load (from 0.22 to 11.82 copies / cell) or condylomata acuminata in men with or without symptoms. Observed any tendency of reduction in viral load with treatment of condylomata acuminata. High viral load did not correlate with increased frequency of relapses and no resistance to treatment with podophyllin. Statistical difference was found when comparing the viral load samples of penile with integrated HPV-16-DNA and samples of penile carcinoma (13.29 vs. 0.22 copies / cell, p = 0.012). This study is pioneer in the investigation of viral load and physical state of HPV-16-DNA in penile non-neoplastic samples.